IP To ATM Conversion Scheme - Yap , Lee Fueng (2004)
In this thesis, a QoS based mapping mechanism for translating both the IntServ and DiffServ QoS seamlessly across the ATM network is designed. An enhancement of the QoS based mapping algorithm with IPv6 flow label deployment has also been proposed. This flow label based mapping algorithm is capable of not only preserving the IntServ and DiffServ QoS end-to-end but also providing some QoSfunctionalities for certain pure IP trafiics that transverse the ATM backbone.